Release and absorption of formaldehyde by textiles - Aldag, Nina; Gunschera, Jan; Salthammer, Tunga (Cellulose (London), 2017)
Formaldehyde has been one of the most widely and most controversially debated substances in indoor spaces. Its classification as a human carcinogen by the International Agency for Research on Cancer in 2004 and the EU in 2015 has given rise to further studies into possible indoor emission sources. It is known that the utilization of formaldehyde-containing chemicals in textiles is widespread. As a result, the question arises as to whether, and to what extent, textiles can contribute to contamination of indoor air with formaldehyde. However, there is hardly any information available on this subject, as the formaldehyde content in textiles is generally determined through extraction procedures. In contrast, the procedure used in this work is focused on the conditions of the indoor space. The release of formaldehyde into the ambient air from various textiles is followed using intensive demand intervals under defined climatic conditions in emission chambers. Additionally, extractions are taken in order to determine the content of free formaldehyde. Doping tests enable the differing properties of various textiles to be investigated with respect to the adsorption and desorption processes of formaldehyde. Through the application of a special double chamber, the diffusion of formaldehyde through textile membranes can be determined. The results demonstrate that extraction procedures do not necessarily correctly reveal the emission behavior of textiles.